1994
DOI: 10.1111/j.1600-0714.1994.tb00065.x
|View full text |Cite
|
Sign up to set email alerts
|

High incidence of H‐ras oncogene mutations in squamous cell carcinoma of lip vermilion

Abstract: Nine specimens of well-differentiated squamous cell carcinoma of the lip vermilion have been analyzed for the presence of H-ras oncogene mutations, using the technique of hybridization with synthetic oligonucleotide probes on in vitro amplified tumour DNA. Five specimens harbored mutations: four in codon 12 and one in codon 13. This high incidence (55%) of mutated H-ras genes suggests that their activation may play an important role in lip tumour development and may be connected to the exposure to chemical and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0
1

Year Published

1996
1996
2016
2016

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(9 citation statements)
references
References 18 publications
0
8
0
1
Order By: Relevance
“…Many of these compounds are known or suspected as carcinogens. In vitro studies support the notion of a close relationship between exposure to environmental chemical carcinogens and the occurrence of Hras oncogene mutations in squamous cell carcinoma of lip vermilion (33). In a cohort study, an excess of lip cancer was reported in association with exposure to chlorine gas, hydrochlorine aerosols, chlorinated aromatics, and sulfur dioxide (34).…”
Section: Discussionmentioning
confidence: 58%
“…Many of these compounds are known or suspected as carcinogens. In vitro studies support the notion of a close relationship between exposure to environmental chemical carcinogens and the occurrence of Hras oncogene mutations in squamous cell carcinoma of lip vermilion (33). In a cohort study, an excess of lip cancer was reported in association with exposure to chlorine gas, hydrochlorine aerosols, chlorinated aromatics, and sulfur dioxide (34).…”
Section: Discussionmentioning
confidence: 58%
“…The incidence of H-ras mutations (22%) in OSCC is in accordance with data in the literature; it varies from 5% in Western countries to 35% in Eastern countries 19,30 . In a study of lower lip tumours in patients at high risk due to smoking habits and sun exposure, in the Serbian population, as much as 55% of cases harboured H-ras gene mutations 25 . Similarly to c-erbB2, an increased rate of H-ras mutations was noted in advanced tumours with nodal metastasis (36%) vs. tumours without metastasis (18%), but without statistical significance.…”
Section: Discussionmentioning
confidence: 99%
“…Hydrolysis of the GTP to GDP terminates the signal. Several studies have identified a frequent occurrence of H-RAS mutation in OCSCC patients, mainly in Asian populations, where it appears to be associated with betel nut chewing [63,79,80].…”
Section: Ras Proteinsmentioning
confidence: 99%